A review of the construction of the supporting energy system for the lunar base - Lei, Song; Guoqing, Zhang; Yaohui, Wang; Chang, Wang; Bo, Liu (Frontiers in Astronomy and Space Sciences, 2025)
Since the 20th century, humanity has entered the era of deep - space exploration. The Moon, being close to Earth, is a key target. Building a lunar base is crucial for space exploration and resource use, but requires a reliable energy system. Existing lunar energy system plans usually concentrate on one or two techs and lack a full - scale analysis of long - term, stable, and adequate energy solutions. This review fills the gap. First, it analyzes lunar environmental conditions like extreme temperature swings, vacuum, and radiation. Then, it offers a detailed historical look at lunar exploration, emphasizing progress from Apollo, Luna, and Chang'E. Next, it delves into eight key lunar-base-suitable energy systems: photovoltaic, solar thermal, thermal, controlled nuclear fusion, nuclear fission reactors, radioisotope thermoelectric generators, fuel cells, and electrostatic power. It carefully weighs each system’s pros and cons regarding energy efficiency, environmental adaptability, and technological viability. Finally, it suggests a phased strategy, integrating different technologies for various base - building stages, aiming to provide a comprehensive framework for future lunar energy system design.